Beneficial Effect of 7-O-Galloyl-D-sedoheptulose, a Polyphenol Isolated from Corni Fructus, against Diabetes-Induced Alterations in Kidney and Adipose Tissue of Type 2 Diabetic db/db Mice. (20th November 2013) - Park, Chan Hum; Noh, Jeong Sook; Park, Jong Cheol; Yokozawa, Takako
Abstract : Traditional medicines are being focused on as possible treatments for diabetes and its complications because of their negligible toxic and/or side effects. In line with this, our group has reported that Corni Fructus, a traditional medicine considered exhibiting beneficial effects on liver and kidney functions, possessed an antidiabetic effect via ameliorating glucose-mediated metabolic disorders. To add to these findings, we screened the iridoid glycoside fraction containing morroniside and loganin, and low molecular weight polyphenol fraction containing 7- O -galloyl-d -sedoheptulose (GS) from Corni Fructus. To our knowledge, GS is a compound only detected in Corni Fructus, and its biological activity has been poorly understood until now. For these reasons, we examined whether GS has an ameliorative effect on diabetic changes using type 2 diabetic db/db mice. Our findings suggest that GS has a beneficial effect on the pathological state of the serum, kidney, and adipose tissue related to diabetic damage.